Determinants of Smoking Behaviour Among Secondary School Students in Bangladesh - Md. Mizanur, Rahman; Sk. Akhtar, Ahmad; Md. Jahirul, Karim; Ho, Ai Chia (Springer US, 2011)
Despite established country’s tobacco control law, cigarette smoking by the young people and the magnitude of nicotine dependence among the students is alarming in Bangladesh. This study was aimed to determine the prevalence of smoking and factors influencing it among the secondary school students. A two-stage cluster sampling was used for selection of schools with probability proportional to enrollment size followed by stratified random sampling of government and private schools. The 70-item questionnaire included ‘core GYTS’ (Global Youth Tobacco Survey) and other additional questions were used to collect relevant information. Analysis showed that the prevalence of smoking was 12.3% among boys and 4.5% among girls, respectively. The mean age at initiation of smoking was 10.8 years with standard deviation of 2.7 years. Logistic regression analysis revealed that boys are 2.282 times likely to smoked than girls and it was 1.786 times higher among the students aged 16 years and above than their younger counterparts. Smoking by teachers appeared to be the strong predictor for students smoking behaviour (OR 2.206, 95% CI: 1.576, 3.088) followed by peer influence (OR 1.988, 95% CI: 1.178, 3.356). Effective smoking prevention program should to be taken to reduce smoking behaviour. The school curricula had less impact in preventing smoking except teacher’s smoking behaviour.